The inSite : Art Practices in the Public Domain San Diego Tijuana. - Barbosa, Felipe; Bradford, Mark; Conwell, Donna; Ferreria, Christopher; Fjellestad, Hans; Gomulicki, Maurycy; Lebrija, Gonzalo; Louro, Joao; Mano, Rubens; Martinez del Cañizo, Itzel; Mik, Aernout; Muntadas, Antoni; et al. (Tijuana : Centro Cultural Tijuana, 2005)
Allora & Calzadilla ; Badgett, Steven ; Barbosa, Felipe ; Bradford, Mark ; Bulbo ; Cruz, Teddy ; Ferreria, Christpher ; Glassford, Thomas ; Gomulicki, Maurycy ; Lebrija, Gonzalo ; Louro, Joao ; Lynch, Matt ; Mano, Rubens ; Martin, Josep Maria ; Martinez del Cañizo, Itzel ; Mik, Aernout ; Muntadas, Antoni ; Parral, José ; R Tj-SD workshop ; Ramirez Jonas, Paul ; Ricalde, Rosana ; Simparch ; Téllez, Javier ; Thauberger, Althea ; Werthein, Judi ; Wrange, Mans
Engels
Spaans
Exhibition. Farsites : Urban crisis and domestic symptoms in recent contemporary art = Sitios distantes. San Diego Museum of Contemporary Art San Diego, 26.08.2005 - 13.11.2005.
boek